The Effect of Therapeutic Group Therapy on Parents’ Ability to Stimulate the Initiative Development for Preschool Children during Covid-19 Pandemic - Muhammad Ari Arfianto; Zahid Fikri; Hening Ryan Aryani; Khikmatul Mu’jizah (Jurnal Keperawatan, 2021)
Introduction: The Covid-19 pandemic causes learning activities to be carried out at home. Parents encounter obstacles in stimulating their child's development because they do not understand how to stimulate and tend to leave it to school. Preschoolers are in the initiative development stage that focus on exploring creativity. Initiative development is preparation for children to cope larger stressors at school age. Objectives: This study aimed to analyze the effect of therapeutic group therapy on the parents’ ability to stimulate initiative development. Methods: This study used one group pre-postest design method. The sample was 32 parents of kindergarten and early childhood education students in Malang City. The independent variable was online therapeutic group therapy. The dependent variable was the parents’ ability to stimulate initiatives development. Results: The results indicated that the average score of the parents' ability to perform stimulation before therapeutic group therapy implementation was 44.19. After therapy, the average score increased to 55.84. Statistical test used Paired T-test showed that the p-value is 0.000 (p-value <0.05), so it can be concluded that therapeutic group therapy had a significant effect on the ability of parents to stimulate initiative development. Conclusions: This study recommends the importance of increasing the parents’ ability to stimulate the pre-school children's initiative development. The school can work together with health workers, especially mental nurses, in therapeutic group therapy activities to increase the parents’ active role in stimulating children's development, thereby optimizing children's psychosocial development.